A Conceptual Framework of Skilled Female Migrant Retention1. Issue 3 (8th June 2015) - Cliff, Katie; Grün, Bettina; Ville, Simon; Dolnicar, Sara
<x xml:space="preserve">Abstract</x> Women make an increasingly important contribution to the skilled workforce. Nations like Australia that suffer skill shortages need not only to attract but also retain more skilled female migrants. The latter has become an important policy issue in Australia because of modest retention rates. While much of the relevant literature focuses upon migrant attraction, we address the retention decision. We derive and empirically test a framework incorporating the key explanatory factors in the decision of skilled female migrants whether to remain in Australia. Our results have important implications for current policy directions.